Toxicity of Legiayu incense as Insecticide and Larvicide Against Aedes aegypti Mosquitoes Mortality - I Made Dwi Mertha Adnyana; Ni Luh Gede Sudaryati; Israil Sitepu (Indonesian Journal of Pharmacy, 2021)
Community-based DHF vector control has been implemented in Indonesia but has not yet obtained optimal results. Thus, in the community choosing synthetic insecticides to control disease vectors. However, irregular and excessive use of insecticides has a toxic effect and resistance to mosquitoes. Burning mosquito coils and incense containing synthetic dyes and fragrances have the potential to reduce environmental quality. Therefore, this research was conducted to analyze the toxicity of Legiayu incense as an insecticide and larvicide against Aedes aegypti mosquito mortality. The research design is experimental with a completely randomized design. Testing was conducted by providing exposure to smoke and ash of Legiayu incense five times on twenty-five Aedes aegypti mosquitoes. Statistical analysis used one-way ANOVA, LSD, and probit test. The test result as insecticide value (p=0.000) effective exposure for 20 minutes with a durability of 6 hours. The test result as larvicide value (p=0.000) effective exposure for 24 hours. Thus, exposure toismoke and ash of iLegiayuiincense has a very noticeable effect on the mortality of Aedes aegypti mosquitoes. Exposureito Legiayu incense smoke obtained an LT50 value of 0,9012 ≤ 5 (super toxic category) with a time of 15 minutes 39 seconds, coefficient determination of 99.24%, and correlation coefficient of 99.62% while exposure to the ash of Legiayu incense obtained LT50 value of 0,05896 ≤ 5 (super toxic category) with time 19 hours 15 minutes 34 seconds, coefficient determination and correlation coefficient of 100%. Histopathological test results showed that Legiayu incense smoke did not cause tissue degeneration, necrosis, hyperplasia, and metaplasia in the lung tissue of mice (mus musculus) within a period of 12 weeks. Thus, Legiayu incense is effective as insecticides and larvicides against Aedes aegypti mosquitoes. Legiayu incense has potential substitute for mosquito repellent coils, temephos, and synthetic incense circulating in the market.